Comorbidities in Anti-Cyclic Citrullinated Peptide Positive At-Risk Individuals Do Not Differ from Those Patients with Early Inflammatory Arthritis - Twigg, Sarah; Nikiphorou, Elena; Nam, Jackie L.; Hunt, Laura; Mankia, Kulveer; Pentony, Peta Elizabeth; Freeston, Jane E.; Tan, Ai Lyn; Emery, Paul (Frontiers in Medicine, 2018)
Objectives: To compare comorbidities in a cohort of cyclic citrullinated peptide (CCP) antibody positive patients without or prior to onset of inflammatory arthritis (IA), to those in patients with early IA. Methods: Baseline data from two established cohorts were used. The first recruited people at risk of IA: CCP antibody positive cases without IA (CCP Cohort, n=296). The second cohort (the Inflammatory Arthritis CONtinuum study, IACON) recruited patients with early IA (n=725). Proportions of patients with given comorbidities were compared between cohorts and then logistic regression was used to determine odds ratios (OR) for the CCP cohort having specific comorbidities, compared to IACON patients. Analyses adjusted for gender, age, smoking status and body mass index. Results: Patients from the CCP cohort were younger (mean age 50, compared to 53 years). The proportion of patients with at least one comorbidity was higher in the IACON than the CCP cohort: (40% compared to 24%, respectively). Results of logistic regression analyses suggested the odds of hypertension, taking a lipid lowering agent, ischaemic heart disease, cerebrovascular disease, lung disease and diabetes were not increased in either cohort. However, patients in the CCP cohort were more likely to be taking an antidepressant (OR = 1.62, 95% CI 1.03, 2.56, p=0.037). Conclusion: There was no significant difference in comorbidities amongst people with CCP antibodies but without inflammatory arthritis, compared to those of patients with established inflammatory arthritis.